2014
DOI: 10.1371/journal.pone.0085915
|View full text |Cite
|
Sign up to set email alerts
|

A CARD9 Polymorphism Is Associated with Decreased Likelihood of Persistent Conjugated Hyperbilirubinemia in Intestinal Failure

Abstract: Recently, genetic associations have been described in intestinal transplants. Namely, Crohn's disease susceptibility gene NOD2 polymorphisms have been reported to be more prevalent in patients with graft failure following intestinal transplantation (IT). Therefore, we sought to determine if polymorphisms in the NOD2 signaling cascade, including NOD2, CARD9, RAC1 and ATG16L1 are associated with intestinal failure (IF) or its complications. We carried out a cross-sectional study of 59 children with IF and 500 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…Human CARD9 genetic mutations may result in protein structure modifications, lower expression, or function loss. CARD9 genetic mutations are associated with inflammatory responses, a susceptibility to fungal infection 45 , 46 , Crohn’s disease 47 , 48 , ulcerative colitis 49 , 50 , intestinal failure 51 , ankylosing spondylitis 52 , 53 , as well as the severity of pulmonary tuberculosis 54 .…”
Section: Card9 Genetic Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human CARD9 genetic mutations may result in protein structure modifications, lower expression, or function loss. CARD9 genetic mutations are associated with inflammatory responses, a susceptibility to fungal infection 45 , 46 , Crohn’s disease 47 , 48 , ulcerative colitis 49 , 50 , intestinal failure 51 , ankylosing spondylitis 52 , 53 , as well as the severity of pulmonary tuberculosis 54 .…”
Section: Card9 Genetic Mutationsmentioning
confidence: 99%
“…The CARD9 mutations, rs4077515, were found to be protective against intestinal failure. One possibility was that this genetic mutations decreased the level of sustained conjugated hyperbilirubinemia and inhibited NOD 2 -dependent signal pathways 51 . The CARD9 mutations rs4077515 significantly decreased the ankylosing spondylitis risk in a HLA-B27-negative Iranian population, possibly by contributing to the CARD9-IL23 axis for the pathogenesis of inflammatory disorders 52 .…”
Section: Card9 Genetic Mutationsmentioning
confidence: 99%
“…While the selected CARD9 SNPs predispose to chronic inflammation in multifactorial inflammatory diseases [ 10 , 14 , 25 , 31 ], their roles in human infections driven by specific microbes, such as Mtb, as shown here, and Candida spp. [ 13 , 19 ], appears limited.…”
Section: Resultsmentioning
confidence: 99%
“…CARD9 is a nonredundant adapter protein which functions in the immune system. As an adaptor protein, CARD9 can coordinate innate and adaptive immune responses, mounting an IFN-γ gut response to pathogens appropriately [ 15 ] and stimulating T cells to differentiate into TH17 cells [ 16 ]. Previous researches have demonstrated that CARD9 was associated with some inflammatory diseases such as tuberculosis, [ 17 ] IBD, [ 18 ] CD [ 9 ] and rheumatoid arthritis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%